Differences in temporal variables and their effect on kinetics in high school pitchers with high and low pitch velocities - Hrudka, B. T.; Dziuk, C.; Cross, J. A. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to compare temporal parameters between high and low velocity high school (HS) pitchers and investigate the influence these parameters have on both pitch speed and upper extremity kinetics. 30 healthy right-handed HS male pitchers with no recent injuries, and clearance to play were included. A 3D motion analysis system was used. Analysis included 15 kinetic and 35 temporal variables. Statistical tests conducted in SPSS. Correlation strength was interpreted as weak, moderate, or strong. High velocity and low velocity throwers showed differences in the timing to progress through the pitching cycle and these temporal variables showed separate relations to pitch speed and kinetics.